Barriers of Additive Manufacturing Adoption in United Arab Emirates Automotive Supply Chain - ALI, ASMA ALI ABDULLA (2023)
The United Arab Emirates (UAE) is one of the leading countries, in the Middle East, for Additive Manufacturing (AM). The UAE government is strongly focusing on fostering innovation within the automotive supply chain of the country. AM offers a tremendous opportunity by improving adaptability and efficiency of the supply chain such as reducing lead times, decreasing the dependence on foreign suppliers, and promoting sustainability in manufacturing processes. The study used a mixed method approach to determine the interrelationship between the barriers and to prioritize them with respect to one another. 11 critical barriers were identified through comprehensive literature review analysis and were modeled using ISM-MICMAC and ANP analysis with opinions gathered from industry experts. The study represents that Lack of standardization, skilled labor shortage, and limited availability of raw materials are the important barriers in the AM adoption. The ISM analysis represented the qualitative classification of barriers levels depending on their influence and interdependence, whereas the ANP analysis provided a quantitative validation for the findings. The results of this study are beneficial in providing insights of AM adoption and the unique obstacles encountered in the UAE automotive supply chain. It also assists the decision makers and automotive industry professionals to strategically implement additive manufacturing initiatives to overcome these barriers.